2017
DOI: 10.1590/1414-431x20176172
|View full text |Cite
|
Sign up to set email alerts
|

Presence of t(14;18) translocation in healthy individuals varies according to ethnic background in the Brazilian population

Abstract: Several groups have demonstrated that healthy individuals can present the t(14;18) translocation. In this report, the presence of the translocation was examined in healthy blood donors in Brazil, a country considered an ethnic melting pot. The translocation was detected by nested PCR in 227 peripheral blood samples from individuals with different ethnic backgrounds. The t(14;18) translocation was found in 45 of 85 White individuals (52.94%); in 57 of 72 Black individuals (79.17%); and in 68 of 70 individuals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…It is unclear if these statistics still hold because the data were obtained almost two decades ago. Over 90% (68/70 people) of Brazilians of Japanese descent harbor t(14;18) cells, and 53% of Caucasians in this series harbored t(14;18) cells in their peripheral blood, which is very similar to previous findings . Thus, the exact proportion of the Japanese population with t(14;18) cells must be further examined.…”
Section: Conclusion and Open Questionssupporting
confidence: 86%
See 1 more Smart Citation
“…It is unclear if these statistics still hold because the data were obtained almost two decades ago. Over 90% (68/70 people) of Brazilians of Japanese descent harbor t(14;18) cells, and 53% of Caucasians in this series harbored t(14;18) cells in their peripheral blood, which is very similar to previous findings . Thus, the exact proportion of the Japanese population with t(14;18) cells must be further examined.…”
Section: Conclusion and Open Questionssupporting
confidence: 86%
“…We have described a new clinical entity-namely, duodenaltype FL. Although patients' clinical course has been clarified, long-term outcome is uncertain because even the longest followed-up cases have not reached 20 years, and only 37 and 53% of Caucasians in this series harbored t(14;18) cells in their peripheral blood, which is very similar to previous findings. 35 Thus, the exact proportion of the Japanese population with t(14;18) cells must be further examined.…”
Section: Conclusion and Open Questionssupporting
confidence: 79%
“…Interestingly, t(14;18) translocation in the peripheral blood was found in 53% (45/85) of white individuals, 79% (57/72) of black individuals, and 97% (68/70) of Japanese-descent. 15 Therefore, further validation is needed to determine whether the difference in the incidence of t(14;18)-positive cells in peripheral blood explains the different incidences of manifested FL across international populations.…”
Section: T(14;18)-positive Cells In Peripheral Blood Of Otherwise Hea...mentioning
confidence: 99%
“…These t(14;18)-positive B cells exist at very low frequency in peripheral blood approximately ranging from 1 × 10 -6 to 1 × 10 -2 , as quantified by quantitative PCR. 5,[8][9][10][11][12][13][14][15] Of note, a study investigated the distribution of t(14;18)-positive cells with a cell sorter and showed that the positive cells are more enriched in IgM memory (median: 380 × 10 -6 ) than in antigen-naive (median: 16 × 10 -6 ) or switched memory (median: 5 × 10 -6 ) B cells. 16 This finding demonstrated that t(14;18) is generated during early B cell development in bone marrow and that affected cells may mature and expand in GCs.…”
Section: T(14;18)-positive Cells In Peripheral Blood Of Otherwise Hea...mentioning
confidence: 99%
“…For example, in 50-60% of healthy adults, the translocation bcl2/IgH was registered, and in 2% − the translocation c-myc/IgH. The proto-oncogene product Bcl2 suppresses the apoptosis, and the protein Myc is a transcriptional factor regulating expression of 15% genes (Levy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%